Cash management and the demand for money - Orr, Daniel (New York : Praeger Publishers, 1971)
The book can be read at two levels: First, to the reader concerned with application to control problems, the results of chapters IV-VI contain a number of potentially applicable generalizations of a basic scheme outlined in chapter III. The first two chapters are useful toward a definition of the control objective, and an understanding of optimization techniques and the cash flow process. Second, the main motivation and thrust of the work is better prediction and understanding of the demand for cash balances, particularly in the business sector.
Includes bibliographical references p. 207-212.
hza 28/08/2018
Loans
Keywords: Cash management; Money; Liquidity (Economics)